PENTAHELIX MODEL COLLABORATION AS A COLLECTIVE EFFORT IN ANTI-CORRUPTION ECOSYSTEMS - Hendrawan Prasetyo; Marynta Putri Pratama; Kus Indarto (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2026)
This study aims to analyze the integration of roles between the government, business sector, civil society, academia, and the media through the Pentahelix framework to create a comprehensive anti-corruption system. This study aims to formulate a strategic collaboration model to close systemic gaps and transform the approach to eradicating corruption into a sustainable collective responsibility. Methodologically, this study uses a descriptive qualitative design to explore the dynamics of intersectoral collaboration. The methods applied include a case study focusing on intersectoral collaboration in corruption eradication efforts. Data collection techniques through data triangulation, which integrates the study of regulatory documentation and official reports with in-depth interviews with representatives from the five pillars of Pentahelix. The data analysis process uses content analysis and thematic analysis techniques through the stages of data reduction, data presentation, and inductive conclusion drawing. The main findings of this study confirm that the effectiveness of corruption eradication is highly dependent on a paradigm shift from sectoral work to interactive collaboration. Synergy between the government, business sector, civil society, academics, and the media is an absolute prerequisite for building a strong anti-corruption ecosystem. Through integrated roles, the Pentahelix model has proven capable of addressing the complexities of corruption more comprehensively.